2013
DOI: 10.1111/opn.12034
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of long term ongoing structured support in early stage of dementia – a case study

Abstract: Findings suggest that structured support groups are a good way to encourage discussions, allow persons with dementia to express themselves and support healthy ageing among partners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 32 publications
(42 reference statements)
1
22
0
Order By: Relevance
“…Two recent systematic reviews reported that informal caregivers need to know information only to manage their own patients appropriately, and they are often overwhelmed by too much information . Therefore, information provision regarding different interventions should be tailored to the needs of each informal caregiver . Some Internet resources were reported to be useful when they provided informal caregivers with information about strategies for managing their own patients' problems and about available welfare services that could potentially fulfil their needs .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two recent systematic reviews reported that informal caregivers need to know information only to manage their own patients appropriately, and they are often overwhelmed by too much information . Therefore, information provision regarding different interventions should be tailored to the needs of each informal caregiver . Some Internet resources were reported to be useful when they provided informal caregivers with information about strategies for managing their own patients' problems and about available welfare services that could potentially fulfil their needs .…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Therefore, information provision regarding different interventions should be tailored to the needs of each informal caregiver. 20,21 Some Internet resources were reported to be useful when they provided informal caregivers with information about strategies for managing their own patients' problems and about available welfare services that could potentially fulfil their needs. 22,23 In the current study, informal caregivers could write questions in the CHR about how to deal with their patient's symptoms, and professionals would answer by describing methods to address those specific symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Thanks to the tangible help from nurses; the older spouse caregivers were able to network with others even without physical in real-life group participation. Another factor with positive influence on the outcome of caregiver support aimed at older spouse caregivers is to receive the support for a longer time period (Chien et al, 2011;Kjallman Alm et al, 2013). In our study, caregivers had used the Internet-based support service for 18 months.…”
Section: Discussionmentioning
confidence: 99%
“…The study aimed at explore how members of existing support groups score on the Sense of Coherence Scale and what they perceive as contributory factors to a meaningful, manageable, and comprehensible everyday life in the presence of dementia. The study is part of a larger project in which we interviewed couples about their experiences in long term ongoing existing support groups [22] as well as well as adult children of persons with dementia to find out what it means for them to have a parent with dementia [23].…”
Section: Rationale For This Studymentioning
confidence: 99%